Application of feed supplement urea molasses multi-nutrient block for ruminants in Hamparan Perak District, Deli Serdang Regency North Sumatra Province - Patriani, Peni; Hafid, Harapin; Sembiring, Iskandar (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Hamparan Perak is a sub-district in Deli Serdang Regency, North Sumatra Province. The main potential in the Hamparan Perak Subdistrict is agriculture, plantation, animal husbandry, and tourism. The livestock sector has developed but when viewed from the aspect of feed management there are several problems faced by farmers. Especially in the quality of feed which is limited to agricultural waste, field grass, and straw as the main feed of livestock grazing. Community service aims to improve the skills and knowledge of farmers about feedmanagement by adding supplement feeds, namely urea molasses multi-nutrient block. The methods used in the community service training and discussion program were previously carried out approaches, interviews, and observation of problems to get a solution. Strengthening and fostering for farmers is carried out after counseling and training activities to achieve maximum results in the development of livestock production. The results thathave been achieved are based on observations and questionnaires after the community service program that is increasing the skills and knowledge of farmers in making and application of supplement feeds, namely urea molasses multi-nutrient block. Farmers' skills in managing feed processing, especially in the preparation of ruminant ration formulations, have also improved